The Financing Behavior of Airline Companies - Kiraci, Kasım; Asker, Veysi (ANDULI, Revista Andaluza de Ciencias Sociales, 2020)
Airline companies, including many legacy airlines, have developed global alliances to adapt to dynamic competitive conditions to gain a competitive advantage over other companies. In this way, the number of destinations and network structures of the airline companies have expanded. This study examines the financial factors affecting the capital structure of airline companies that are members of global alliances. In this context, the goal of this study is to reveal the financing behaviors of airlines using theories related to the structure of capital. To this end, we used secondary financial data of member airlines in strategic alliances. For the scope of the study, the period of 2005-2017 was examined, and the panel data analysis method was used. Empirical results of the study indicate that: a) There are significant differences between short-term and long-term debt behaviors of the airlines that were analyzed, b) While long-term debt behavior of airlines is in accordance with the Trade-Off Theory, short-term debt behavior is in accordance with the Pecking Order Theory, and c) In the global alliances, the long-term financial behavior is similar to the traditional low-cost business model of airlines.